Development Economics and the issues of poverty and social inequalities - Piasecki, Ryszard (Annales. Etyka w Życiu Gospodarczym, 2019)
Development economics emerged as a separate discipline of economic science in the 1950s but it wasn’t until the 1960s and mid-1970s that it began to draw serious attention. Gradually, an extensive literature concerning economic development was built up. In the 1980s it turned out, however, that despite some successes, the economic growth in most of medium and less developed countries was not as high as expected. During the 1980s and 1990s, the so-called Washington Consensus dominated the theory and practice of economic development. This notion covered the whole range of activities that were to lead the developing countries to improved welfare and prosperity. It included strict fiscal and monetary policies, deregulation, foreign trade and capital flow liberalisation, elimination of government subsidies, moderate taxation, liberalisation of interest rates, maintaining low inflation, etc. Based on the developmental experience of over past ten years, a new paradigm of development is emerging, the elements of which can be described as follows: (1) the basic economic environment should encourage the long-term investment in (2) the economy should have a high sensitivity to market stimuli (3) human capital must complement physical capital (4) due to the fast flow and absorption of information in the rapidly changing world, the key role is played by institutions and mechanisms that jointly respond to stimuli (5) wherever market failures occur, an intervention of the state should be market-friendly 6) social equality must be guaranteed if the economic development is to take place on a sustainable basis.